Synthesis, Biological Evaluation and Study of the Effect of Various N-Substituents on the Thermal Stabilities of Some New Diethanolamine Derivatives - Akhtar, Muhammad Nadeem; Yar, Muhammad; Mushtaq, Nafeesa; Afzal, Sadia; Khan, Abdul Samad; Khan, Islam Ullah; Seema, Zareen; Shahzad, Sohail Anjum; Khan, Zulfiqar Ali; Naqvi, Syed Ali Raza; Mahmood, Nasir; Tahir, Lubna (Asian J. Chem, 2013)
Diethanolamine and its derivatives are of considerable interest in medicinal and other industrial products. A series of new diethanolamine derivatives has been synthesized and characterized by 1H NMR, 13C NMR, FTIR and mass spectrometry. All synthesized compounds have been tested for their in vitro antibacterial activity against pathogenic microorganisms Escherichia coli, Staphylococcus aureus, Micrococcus luteus, Pseudomonas aeruginosa, Bacillus subtilis, Pasteurrella mutocida, Rhizopus oryzae and Salmonella typhi. Among the tested compounds, compounds 2a, 2b, 2c, 3a and 4b have been found to be most potent members, which inhibited most of the pathogens used in the assay. Diethanolamine must posses tosyl or trifluoro groups in order to have good antimicrobial activities. All synthesized derivatives exhibited average FRAP activity and considerably good metal chelating activity and compound 2c showed excellent ABTS radical scavanging among all tested derivatives. Thermal stability and the effect of various N-protected groups on the thermal stability and degradation of selected diethanolamine derivatives (free flowing oils at room temperature and solid derivative 2a) has been studied by TGA and DSC analysis.